Impedance Tube Method Based On Arduino For Material Acoustic Measurement - Anwar, Suci; Yohandri, Yohandri; Darvina, Yenni; Yulkifli, Yulkifli (Journal of Experimental and Applied Physics, 2025)
Acoustics play a crucial role in advancing technology and industry by mitigating moise, which is an uwanted byproduct of many devices. However, existing tools for testing acoustic properties often lack automation and calibration, which limits their realibility and usability. This study introduces the development of a test device designed to measure the sound absorption coefficient of materials using the two-microphone impedance tube method. The device incorporates a PVC tube, an Arduino Nano Microcontroller, and an OLED display for real-time data analysis and visualization. The proposed device offers simplicity, portability, and improved measurement accuracy compared to existing solutions. The method involves measuring sound intensity and absorption coefficients using direct dan indirect techniques. Experimentals results demonstrate that the device achieves an average accuracy rate of 20.38%, with consistent absorption coefficient values across repeated tests. The frequency range tested aligns with the performance limits of the device, further confirming its reliability. In conclusion, the developed device provides a practical and reliable solution for testing acoustic materials, addressing the limitations of previous methods.